2019
DOI: 10.1155/2019/8609682
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Low- or High-Permeability Inclusion on Free Convection in a Porous Medium

Abstract: Density-driven free convection in porous media is highly affected by large-scale heterogeneity, typical of which are low- or high-permeability inclusions imbedded in homogeneous porous media. In this research, we applied the modified Elder problem to investigate the impact of low- or high-permeability inclusions on the migration of a dense, unstable salt plume. Sensitivity analyses were conducted in terms of the permeability contrast, the effective area (the area of the inclusion beneath the source zone), and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 40 publications
1
3
0
Order By: Relevance
“…Free convection following vertical seawater infiltration is likely an important mechanism driving fast salinization of the groundwater system, particularly at the early stages of the simulation period when the coastline was quickly shifting landward (Kooi et al., 2000). Vertical seawater infiltration velocities were in the order of meters to tens of meters per year, which agrees with high rates of free convection reported for numerical studies (Xie et al., 2011; Yan et al., 2019) as well as field sites characterized by highly permeable geology (Delsman et al., 2014; Post & Kooi, 2003). The fast vertical salinization process linked to marine transgression implicates permeable sandy coastal groundwater systems that paleo‐modeling domains do not necessarily have to be extended until the position of the paleo‐coastline at the model start.…”
Section: Discussionsupporting
confidence: 85%
“…Free convection following vertical seawater infiltration is likely an important mechanism driving fast salinization of the groundwater system, particularly at the early stages of the simulation period when the coastline was quickly shifting landward (Kooi et al., 2000). Vertical seawater infiltration velocities were in the order of meters to tens of meters per year, which agrees with high rates of free convection reported for numerical studies (Xie et al., 2011; Yan et al., 2019) as well as field sites characterized by highly permeable geology (Delsman et al., 2014; Post & Kooi, 2003). The fast vertical salinization process linked to marine transgression implicates permeable sandy coastal groundwater systems that paleo‐modeling domains do not necessarily have to be extended until the position of the paleo‐coastline at the model start.…”
Section: Discussionsupporting
confidence: 85%
“…Among the newest advancements in the Elder problem, we can outline the following studies. Yan et al (2019) [20] applied the modified Elder problem to investigate the impact of permeability inclusions on the migration of an unstable salt plume. Shafabakhsh et al (2019) [21] investigated the fractured Elder problem, that is, the influence of different fracture networks on the Elder problem using the finite element method (FEM).…”
Section: Existing Approaches To the Elder Problemmentioning
confidence: 99%
“…Studies on heterogeneous fields are usually limited to qualitative analysis of the effect of heterogeneity Yan et al, 2019;Wang et al, 2021;. Heterogeneity in permeability plays an important role in onset, growth, maintenance and decay of the GDC and the dissolution rate .…”
Section: Introductionmentioning
confidence: 99%
“…It is found that GDC depends to a large extent on properties of the formation (e.g., the permeability and porosity) and of the brine phase (e.g., the relation between brine density and concentration of dissolved CO 2 , viscosity and molecular diffusion coefficient) . For instance, researchers find a linear relation between the dissolution rate and the intrinsic permeability for isotropic homogeneous media Studies on heterogeneous fields are usually limited to qualitative analysis of the effect of heterogeneity Yan et al, 2019;Wang et al, 2021;. Heterogeneity in permeability plays an important role in onset, growth, maintenance and decay of the GDC and the dissolution rate .…”
Section: Introductionmentioning
confidence: 99%